Parabolic trough solar collector for low enthalpy processes: An analysis of the efficiency enhancement by using twisted tape inserts. (August 2016) - Jaramillo, O.A.; Borunda, Mónica; Velazquez-Lucho, K.M.; Robles, M.
Abstract: Concentrated solar energy is a promising source of energy which is currently attracting many efforts to enhance its exploitation. In particular, parabolic trough collectors for low enthalpy processes is an emerging technology. Lately, many work is done focused on the improvement of these devices. One technique to achieve this is by augmenting the heat transfer in the receiver tube by inserting a twisted tape in the tube. In this work, we develop a thermodynamic model framework to analyse the performance of a parabolic trough collector with a twisted tape insert. We find the set of conditions under which a twisted tape insert is useful to boost the performance of a parabolic trough collector. This set of conditions corresponds to devices with low twisted ratios operating at low Reynolds numbers. The proposed model is supported with experimental data. Highlights: Parabolic trough collectors with a twisted tape insert. Solar thermal collector for low enthalpy processes. Exergetic analysis of a parabolic trough collector. Heat transfer enhancement. Thermodynamic analysis by the Second Law.